Feeding ecology of blue whiting (Micromesistius poutassou) in the NW Mediterranean: The important role of Myctophidae. (December 2020) - Mir-Arguimbau, Joan; Navarro, Joan; Balcells, Marc; Martín, Paloma; Sabatés, Ana
Abstract: We investigated the feeding ecology of blue whiting ( Micromesistius poutassou ) in the NW Mediterranean living in two habitats, the shelf break and the continental slope, throughout the year, by combining two methodological approaches, stomach content characterization and stable isotope analyses. Stomach content indicated that blue whiting mainly fed on Myctophidae fish, decapods and euphausids. Differences in diet were observed between areas and throughout the year, with a higher proportion of Myctophidae in individuals living over the shelf break (attaining values 70% weight) than over the slope (attaining values 50% weight). In both habitats Myctophidae, a highly energetic prey, were mainly consumed in spring and summer, which might allow the species to recover energy reserves after the reproductive period and supply the energetic demands of the fast growth season. MixSIAR models, which provide estimates of the relative contribution of each prey to the diet of the consumer by combining stable isotope values of the consumer with those of their potential prey, also indicated that Myctophidae were the main prey in the assimilated diet over the entire year, in both areas. The trophic niche, measured by isotope analyses, suggested segregation between individuals of the shelf break (mainly immatures) and the slope (mainly adults), which would reduce the intraspecific competition. The seasonal and spatial differences observed in the feeding ecology of the Mediterranean blue whiting are related to the energetic requirements of the species throughout the year and with changes in the spatial distribution of the different ontogenetic phases. Highlights: Variability in the diet of blue whiting between areas and throughout the year. Myctophids are the main prey in the diet of Mediterranean blue whiting. Myctophids supply the energetic demands for blue whiting post-breeding recovery. Trophic segregation between young and adult specimens of blue whiting. Blue whiting has a higher trophic level in the Mediterranean than in the Atlantic.